2010
DOI: 10.1089/apc.2009.0214
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Contexts of Inconsistent Condom Use Among Heterosexual Men and Women Living with HIV in India: Implications for Prevention

Abstract: This investigation examined sexual behaviors among heterosexual persons living with HIV (PLHIV) in India. Study participants (mostly married) were interviewed during August to November 2006 in five Indian states using a quantitative survey (n ¼ 100 men and 100 women), eight focus groups (n ¼ 58 participants), and in-depth interviews (n ¼ 31). One third of men and one fourth of women reported inconsistent condom use with regular sexual partners. Facilitators of condom use with regular partners included a feelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
58
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 34 publications
6
58
1
1
Order By: Relevance
“…The association between consistent condom use and duration of time on ART has been reported in other studies [13] [22] [26]. We also found that longer ART use was significantly associated with consistent condom use.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The association between consistent condom use and duration of time on ART has been reported in other studies [13] [22] [26]. We also found that longer ART use was significantly associated with consistent condom use.…”
Section: Discussionsupporting
confidence: 88%
“…The on-going counselling and HIV prevention messages provided at ART initiation and follow up has contributed to reductions in sexual risk behaviours. Furthermore, it had been shown that when persons receiving ART accept their illness and adjust to being HIV positive, they are likely to modify sexual behaviours [1] [26]. Therefore, strengthening the provision of secondary prevention messages and risk-reduction interventions in ART programs creates an enabling environment for reduction of risky sexual behaviours [13] [22].…”
Section: Discussionmentioning
confidence: 99%
“…25,26 While rates of consistent condom use among couples who are aware of their status are higher, unprotected sex among these couples is still common 27,28 and has been shown to be associated with desire for pregnancy 29 and alcohol use. 30 PLHIV who inconsistently use condoms and who simultaneously have higher viral loads due to non-adherence to antiretroviral treatment (ART) or because they are not yet eligible for ART are at high risk for transmitting HIV to negative sex partners. [31][32][33] These individuals are also at higher risk for acquiring other sexually transmitted infections which could compromise their own health.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, behavioral interventions especially tailored for condom use promotion among women living with HIV are still scarce, which could explain why subgroup analyses could not find differences in intervention effects, based on whether they were exclusively tailored for women. Despite repeated research findings indicating the challenges faced by women living with HIV, more studies are needed to understand how gender-linked factors (e.g., skill-building to negotiate condom use, gender violence, and gender power imbalances regarding economic resources and employment) influence the effectiveness of behavioral interventions to promote condom use 16,54,55 . A recent systematic review of behavioral interventions to improve contraceptive use for family planning among women living with HIV also found limited evidence to compare the interventions' results 56 .…”
Section: Discussionmentioning
confidence: 99%
“…We recommend that behavioral interventions focusing on condom use promotion among women living with HIV could have greater public health impact if they were part of broad positive prevention programs delivered with a gender perspective (including women-initiated prevention options) and developing actions that involve male partners, family planning counseling, community empowerment, mental health and drug abuse treatment, and safe serostatus disclosure settings 11,55 . As seen in the qualitative syntheses, few studies included issues beyond sexual risk behavior and none approached family planning or included women's partners.…”
Section: Discussionmentioning
confidence: 99%